Oceanic Uptake of Oxygen During Deep Convection Events Through Diffusive and Bubble‐Mediated Gas Exchange. Issue 10 (26th October 2017) - Sun, Daoxun; Ito, Takamitsu; Bracco, Annalisa
Abstract : The concentration of dissolved oxygen (O2 ) plays fundamental roles in diverse chemical and biological processes throughout the oceans. The balance between the physical supply and the biological consumption controls the O2 level of the interior ocean, and the O2 supply to the deep waters can only occur through deep convection in the polar oceans. We develop a theoretical framework describing the oceanic O2 uptake during open‐ocean deep convection events and test it against a suite of numerical sensitivity experiments. Our framework allows for two predictions, confirmed by the numerical simulations. First, both the duration and the intensity of the wintertime cooling contribute to the total O2 uptake for a given buoyancy loss. Stronger cooling leads to deeper convection and the oxygenation can reach down to deeper depths. Longer duration of the cooling period increases the total amount of O2 uptake over the convective season. Second, the bubble‐mediated influx of O2 tends to weaken the diffusive influx by shifting the air‐sea disequilibrium of O2 toward supersaturation. The degree of compensation between the diffusive and bubble‐mediated gas exchange depends on the dimensionless number measuring the relative strength of oceanic vertical mixing and the gas transfer velocity. Strong convective mixing, which may occur under strong cooling, reduces the degree of compensation so that the two components of gas exchange together drive exceptionally strong oceanic O2 uptake. Key Points: We develop a new theoretical framework describing the air‐sea transfer of O2 during open‐ocean deep convection events Both the duration and the intensity of the heat flux contribute to the total O2 uptake The O2 bubble‐mediated flux can be compensated by the reduction in diffusive gas flux depending on the strength of vertical mixing